Association between dimensions of trauma-related psychopathology and asthma in trauma-exposed women - Lin, Esther R.-H.; Roeckner, Alyssa R.; Fani, Negar; Merrill, Natalie; Gillespie, Charles F.; Ely, Timothy D.; Bradley, Bekh; Michopoulos, Vasiliki; Powers, Abigail; Jovanovic, Tanja; Stevens, Jennifer S. (Frontiers in Behavioral Neuroscience, 2023)
Exposure to traumatic events and stressful life experiences are associated with a wide range of adverse mental and physical health outcomes. Studies have found post-traumatic stress disorder (PTSD), depression, and anxiety sensitivity occurrence to be common in addition to inflammatory diseases like asthma, especially in women. Moreover, overlapping neurobiological mechanisms have been linked to both PTSD and asthma. In the current study, n=508 women reported on presence of lifetime asthma diagnosis and symptoms of trauma-related psychopathology including PTSD and depression. A separate group of female participants (n=64) reported on asthma, PTSD, depression and anxiety sensitivity, and underwent functional MRI scans during a fearful faces task, and their anterior insula responses were analyzed. Overall, PTSD and depression severity were significantly higher in those with asthma versus those without asthma. There was a positive association between anterior insula response to social threat cues and depression symptoms only among individuals without a lifetime presence of asthma. These findings provide continued evidence on the interactions between stress, neural mechanisms involved in interoception and salience detection, and trauma-related psychopathology.